Inducing Sadness and Anxiousness through Visual Media: Measurement Techniques and Persistence - Kuijsters, Andre; Redi, Judith; de Ruyter, Boris; Heynderickx, Ingrid (Frontiers in Psychology, 2016)
The persistence of negative moods (sadness and anxiousness) induced by three visual Mood Induction Procedures (MIP) was investigated. The evolution of the mood after the MIP was monitored for a period of 8 minutes with the Self-Assessment Manikin (every 2 minutes) and with recordings of skin conductance level (SCL) and electrocardiography (ECG). The SAM pleasure ratings showed that short and longer film fragments were effective in inducing a longer lasting negative mood, whereas the negative mood induced by the IAPS slideshow was short lived. The induced arousal during the anxious MIPs diminished quickly after the mood induction; nevertheless, the SCL data suggest longer lasting arousal effects for both movies. The decay of the induced mood follows a logarithmic function; diminishing quickly in the first minutes, thereafter returning slowly back to baseline. These results reveal that caution is needed when investigating the effects of the induced mood on a task or the effect of interventions on induced moods, because the induced mood diminishes quickly after the mood induction.